The roles, challenges and prospects of women expatriate in MNCs: An overview - Yusof, Ab. Aziz; Ali, Juhary (Universiti Utara Malaysia, 2002)
One of the most significant features of the global labour market in the last half of the twentieth century has been the increasing labour force participation rate of women. Despite this, women participation in managerial still remains scarce.As commercial activity becomes increasingly internationalized, there is coresponding increase in the need for international managers. However, it is evident from the extent research that women are not progressing to senior international management positions at comparable rates to their male counterparts. Previous research has estimated that only 3 percent of expatriate managers are women. The small percentages notwithstanding, women have been observed as effective in overseas positions. The number of women expatriate is increasing steadily over the year with slow progress. This paper draws a clear picture of phenomenon that men expatriate is out number of women expatriate in the business world. It provides details how to increase the number of women expatriate in handling international management and specific challenges that will face by the women expatriate.